PENGALAMAN IBU MERAWAT ANAK PENDERITA ASMA YANG MENGALAMI MASALAH KUALITAS HIDUP - ., Monalisa (JURNAL HEALTH AND SPORT, 2013)
Asthma in children is a problem for patients and families because it can have an impact relating to the quality of life of children. This study aims to obtain a picture of mother's experience in treating children with asthma who experience problems of quality of life. The qualitative study used descriptive phenomenology method. Participants in this study amounted to 7 people. The analysis using analytical methods Collaizi. The results of this study identified seven themes: (1) assessment of mothers of asthmatic attacks in children (2) assessment of the quality of life of children (3) roles and responsibilities of the mother (4) the problems and difficulties faced by mothers (5) social support (6) the meaning maternal experience (7) hope to improve health services. The study is expected to provide an overview of asthma management is given to mothers in caring for children with asthma with the issue of quality of life.